Continuous MOF (Metal Organic Framework) film with three-dimensional grid interface as well as preparation method and application thereof
By forming an α-Co(OH)2 grid layer on the polymer support and riveting metal ions, a continuous MOF film with a three-dimensional grid interface was prepared, which solved the problems of MOF film preparation and interface compatibility in the prior art, and achieved high-performance MOF film preparation.
Patent Information
- Application Number
- CN202411635599.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The prior art is difficult to prepare continuous defect-free MOF films on polymer support, and the interface compatibility between MOFs and polymer support is poor, resulting in poor separation selection performance, limiting the industrial application of MOF films.
The base film is composed of a polymer support layer, a polysulfone layer and a nonwoven fabric layer. The α-Co(OH)2 grid layer is formed by diffusion of PVA-cobalt ion aqueous solution and ligand solution, and the metal ions are riveted in the metal salt solution, and finally reacted in the ligand solution to prepare a continuous MOF film with a three-dimensional grid interface.
A continuous defect-free three-dimensional grid interface MOF membrane was successfully prepared, which solved the problem of MOF membrane preparation on polymer support, improved the separation selection performance and density of the membrane, and was suitable for gas separation and other fields.
Smart Images

Figure CN119607924A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of MOF membranes, and in particular relates to a continuous MOF membrane with a three-dimensional grid interface and a preparation method and application thereof. Background Art
[0002] Membrane separation technology is widely used in the fields of medicine, food, biology, energy, seawater desalination and gas separation due to its advantages of simple operation, low energy consumption, high processing efficiency, no secondary pollution, and separation and purification functions. It has great application prospects and is considered to be a separation technology with great potential. In the membrane application process, membrane materials with good separation selectivity and high permeation rate are the core of membrane separation technology, which determines the selective permeability, process design, membrane stability and the final membrane separation applicable system.
[0003] Metal-organic frameworks (MOFs) are crystalline porous materials with a periodic network structure formed by the self-assembly of inorganic metal centers (metal ions or metal clusters) and bridging organic ligands. MOFs have various advantages such as high porosity, large specific surface area and regular pore size, which makes them play a leading role in the membrane separation process and become one of the preferred materials in many application fields.
[0004] At present, since the preparation of most MOF materials requires organic solvents, and the polymer support has obvious swelling phenomenon to organic solvents, most of the existing MOF membrane preparation processes are to load metal salts or ligands on the surface of the inorganic support layer, and very few MOF membranes are prepared on low-cost, high-processability polymer supports. In addition, even if a small number of MOF membranes are prepared on polymer supports, the interface compatibility between MOFs and polymer supports is poor, and defects are easily generated, which leads to poor separation selectivity of the prepared membrane, greatly limiting the industrial application of MOF membranes. Summary of the invention
[0005] In order to overcome the technical problems in the related art such as the difficulty in preparing different types of continuous defect-free MOF membranes on polymer supports and the interface compatibility between MOFs and the interface layer, the purpose of the present invention is to provide a continuous MOF membrane with a three-dimensional grid interface and a preparation method and application thereof. The preparation method has a simple preparation process and obviously solves the problem of the difficulty in preparing different types of continuous defect-free MOF membranes and interface compatibility on polymer supports, thereby obtaining different types of continuous defect-free metal-organic skeleton membranes with three-dimensional grid interfaces.
[0006] In a first aspect of the present invention, a method for preparing a continuous MOF membrane having a three-dimensional grid interface is provided, wherein the base membrane of the continuous MOF membrane is formed by laminating a polymer support layer, a polysulfone layer and a non-woven fabric layer sequentially arranged from top to bottom, wherein the polymer support layer is a polydimethylsiloxane layer, and the preparation method comprises the following steps:
[0007] S1. After diffusing the PVA-cobalt ion aqueous solution from the polydimethylsiloxane layer into the base film, the first ligand solution is reversely diffused from the non-woven fabric layer into the base film to coordinate with the cobalt ions in the PVA-cobalt ion aqueous solution, forming an α-Co(OH)2 grid layer on the surface of the polydimethylsiloxane layer, and obtaining a membrane having an α-Co(OH)2 grid layer;
[0008] S2. The membrane having the α-Co(OH)2 mesh layer is immersed in a metal salt solution to fix the metal ions in the metal salt solution on the α-Co(OH)2 mesh layer. The membrane is taken out and dried, and then immersed in a second ligand solution for reaction to obtain the continuous MOF membrane having a three-dimensional mesh interface.
[0009] In some embodiments of the present invention, step S1 is specifically as follows: the polydimethylsiloxane layer of the base film is suspended upward and fixed, the PVA-cobalt ion aqueous solution is poured into the polydimethylsiloxane layer and soaked for 30-50 minutes, then horizontally placed in the first ligand solution, soaked for 10-60 seconds, taken out, washed, and dried.
[0010] In some embodiments of the present invention, in step S2, the immersion in the second ligand solution specifically comprises: immersing the polydimethylsiloxane layer downward in the second ligand solution for reaction for 3-6 hours.
[0011] In some embodiments of the present invention, the solvent of the first ligand solution is methanol or ethanol.
[0012] In some embodiments of the present invention, the ligand of the first ligand solution is 2-methylimidazole.
[0013] In some embodiments of the present invention, the concentration of the first ligand solution is (2.5-3.5) g / mL.
[0014] In some embodiments of the present invention, the metal salt solution is a cobalt salt solution or a zinc salt solution, and the ligand in the second ligand solution is 2-methylimidazole; or, the metal salt solution is a copper salt solution, and the ligand in the second ligand solution is trimesic acid.
[0015] In some embodiments of the present invention, the solvent of the metal salt solution is a mixture of a strong polar solvent and water, and the strong polar solvent is methanol or ethanol.
[0016] In some embodiments of the present invention, the volume ratio of the strong polar solvent to water is 1:(1-4).
[0017] In some embodiments of the present invention, the concentration of the ligand in the second ligand solution is (2.5-3.5) g / mL.
[0018] The second aspect of the present invention provides a continuous MOF membrane having a three-dimensional grid interface prepared by the above-mentioned preparation method.
[0019] The third aspect of the present invention provides an application of the above-mentioned continuous MOF membrane with a three-dimensional grid interface in gas separation.
[0020] The embodiments of the present invention provide a continuous MOF membrane with a three-dimensional grid interface and a preparation method and application thereof, which have at least one of the following advantages:
[0021] (1) The present invention first forms a two-dimensional nanosheet grid layer on the polymer support layer of the base membrane, and then based on the two-dimensional nanosheet grid layer, the metal ions are first fixed on the grid layer through the gradient phase diffusion method, and then combined with the ligand molecules, thereby successfully preparing a continuous and dense MOF membrane combining two-dimensional and three-dimensional structures. The MOF membrane has excellent separation selectivity for different gas systems.
[0022] (2) The present invention utilizes the instability of MOF in aqueous solution (MOF will decompose into two-dimensional nanosheets in aqueous solution) to form a large-area continuous and defect-free two-dimensional nanosheet grid layer on the surface of the polymer support, thereby avoiding direct contact between the organic solvent and the polymer support in the subsequent steps, thereby solving the swelling problem caused by direct contact between the organic solvent and the polymer support.
[0023] (3) Since the first ligand solution in the present invention combines with the metal ions through reverse diffusion, there are still some metal ions in the grid layer that have not combined with the ligand molecules in the first ligand solution. Therefore, the two-dimensional nanosheet grid layer formed in the present invention also plays a role in pre-embedding metal ions. These partially embedded metal ions and the metal ions later riveted on the interface can combine with the ligand molecules in the second ligand solution, which can solve the problem of uneven riveting of metal ions in the later stage, thereby strengthening the heterogeneous nucleation on the interface layer and enhancing the continuity and density of the MOF membrane.
[0024] (4) Since the technical solution provided by the present invention can effectively solve the swelling problem caused by direct contact of the organic solvent with the polymer support, it can be applied to the preparation of various MOF membranes. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] These and / or other aspects and advantages of the present invention will become apparent and readily understood from the following description of preferred embodiments in conjunction with the accompanying drawings, in which:
[0026] Figure 1 The morphology characterization diagram of the α-Co(OH)2-1 mesh layer: (1) SEM image of the α-Co(OH)2-1 mesh layer at low magnification; (2) SEM image of the α-Co(OH)2-1 mesh layer at high magnification; (3) SEM image of the cross section of the α-Co(OH)2-1 mesh layer; (4) AFM image of the α-Co(OH)2-1 mesh layer;
[0027] Figure 2 This is a picture of the ZIF-67-1 membrane: Figure 2 -(a) and Figure 2 -(b) is the surface SEM image at different magnifications, Figure 2 -(c) is the cross-sectional SEM morphology image, Figure 2 -(d) is the AFM image;
[0028] Figure 3 The morphology and structure characterization diagram of the α-Co(OH)2-2 grid layer: Figure 3 -(a) is the morphology of the α-Co(OH)2-2 grid layer; Figure 3 -(b) is the XRD spectrum of α-Co(OH)2-2 mesh layer obtained under simulation and experimental conditions; Figure 3 -(c) is the FTIR spectrum of the α-Co(OH)2-2 mesh layer, Figure 3 -(d) is the TG analysis spectrum of the α-Co(OH)2-2 grid layer;
[0029] Figure 4 The morphology characterization diagram of the α-Co(OH)2-2 mesh layer: (1) SEM image of the α-Co(OH)2-2 mesh layer at low magnification; (2) SEM image of the α-Co(OH)2-2 mesh layer at high magnification; (3) SEM image of the cross section of the α-Co(OH)2-2 mesh layer; (4) AFM image of the α-Co(OH)2-2 mesh layer;
[0030] Figure 5 For the morphology characterization of ZIF-67-2 membrane: Figure 5 -(a) and Figure 5 -(b) is the surface SEM image at different magnifications, Figure 5 -(c) is the cross-sectional SEM morphology image, Figure 5 -(d) is the AFM image;
[0031] Figure 6 For the structural characterization of ZIF-67-2 membrane; Figure 6-(a) N2 adsorption-desorption isotherm and specific surface area at 77K; Figure 6 -(b) is the CO2 and N2 gas adsorption isotherms of ZIF-67-2 membrane; Figure 6 -(c) is the CH4 and N2 gas adsorption isotherms of ZIF-67-2 membrane; Figure 6 -(d) is the C3H6 and C3H8 gas adsorption isotherms of ZIF-67-2 membrane;
[0032] Figure 7 This is a morphology characterization diagram of the α-Co(OH)2-3 grid layer: Figure 7 -(1) is a SEM image of the α-Co(OH)2-3 mesh layer at low magnification; Figure 7 -(2) is a SEM image of the α-Co(OH)2-3 mesh layer at high magnification; Figure 7 -(3) is a cross-sectional SEM image of the α-Co(OH)2-3 mesh layer; Figure 7 -(4) is the AFM image of the α-Co(OH)2-3 mesh layer;
[0033] Figure 8 For the morphology characterization of ZIF-67-3 membrane: Figure 8 -(a) and Figure 8 -(b) is the surface SEM image at different magnifications, Figure 8 -(c) is the cross-sectional SEM morphology image, Figure 8 -(d) is the AFM image;
[0034] Fig. 9 For the morphology characterization of ZIF-8 membrane: Fig. 9 -(a) and Fig. 9 -(b) is the surface SEM image at different magnifications;
[0035] Fig.10 For the morphology characterization of CuBTC film: Fig.10 -(a) and Fig.10 -(b) is the surface SEM image at different magnifications;
[0036] Fig.11 For the morphology characterization of ZIF-67-4 membrane: Fig.11 -(a) and Fig.11 -(b) is the surface SEM image at different magnifications;
[0037] Fig.12 For the morphology characterization of ZIF-67-5 membrane: Fig.12 -(a) and Fig.12 -(b) is the surface SEM image at different magnifications;
[0038] Fig.13 The gas separation performance of the ZIF-67-1, ZIF-67-2, and ZIF-67-3 membranes prepared in Examples 1-3: Fig.13 -(a) is the permeation rate of CH4 for ZIF-67-1, ZIF-67-2, and ZIF-67-3 membranes under pure gas conditions; Fig.13 -(b) N2 permeation rate of ZIF-67-1, ZIF-67-2, and ZIF-67-3 membranes under pure gas conditions; Fig.13 -(c) CH4 / N2 separation selectivity of ZIF-67-1, ZIF-67-2, and ZIF-67-3 membranes under pure gas conditions;
[0039] Fig.14 The gas separation performance of the ZIF-67-1, ZIF-67-2, and ZIF-67-3 membranes prepared in Examples 1-3: Fig.14 -(a) is the permeation rate of CO2 of ZIF-67-1, ZIF-67-2, and ZIF-67-3 membranes under pure gas conditions; Fig.14 -(b) N2 permeation rate of ZIF-67-1, ZIF-67-2, and ZIF-67-3 membranes under pure gas conditions; Fig.14 -(c) CO2 / N2 separation selectivity of ZIF-67-1, ZIF-67-2, and ZIF-67-3 membranes under pure gas conditions;
[0040] Fig.15 is the gas separation performance of the ZIF-67-2 membrane prepared in Example 2; Fig.15 -(a) The permeation rate of ZIF-67-2 membrane to C3H6 and C3H8 and the separation selectivity of C3H6 / C3H8 under pure gas conditions; Fig.15 -(b) The permeation rate of ZIF-67-2 membrane to C3H6 and C3H8 and the separation selectivity of C3H6 / C3H8 under mixed gas conditions;
[0041] Fig.16 is the gas separation performance of the CuBTC membrane prepared in Example 5; Fig.16 -(a) The permeation rate of CH4 and N2 and the separation selectivity of CH4 / N2 of CuBTC membrane under pure gas conditions; Fig.16 -(b) The permeation rate of CO2 and N2 and the separation selectivity of CO2 / N2 of CuBTC membrane under pure gas conditions; Fig.16 -(c) The permeation rate of CuBTC membrane to C3H6 and C3H8 and the separation selectivity of C3H6 / C3H8 under pure gas conditions. DETAILED DESCRIPTION
[0042] The technical solution of the present invention is further specifically described below by examples and in conjunction with the accompanying drawings. In the specification, the same or similar reference numerals indicate the same or similar components. The following description of the embodiments of the present invention with reference to the accompanying drawings is intended to explain the overall inventive concept of the present invention and should not be construed as a limitation of the present invention.
[0043] The models and manufacturers of the instruments used in the various embodiments of this application are as follows:
[0044] Field emission electron scanning microscope (SEM), model: DropShapeAnalyzer100, manufactured by Bruker, Germany;
[0045] Atomic force microscope (AFM), model: TensorII, produced by Hitachi, Japan;
[0046] Specific surface area and porosity analyzer (BET), model: Micromeritics, ASAP2020PlusHD88, produced by Micromeritics, USA;
[0047] X-ray diffraction (XRD), model: D2Discoverdiffractometer, produced by Bruker, Germany;
[0048] Fourier transform infrared spectrometer (FTIR), model: ALPHAII, produced by Bruker, Germany;
[0049] Thermogravimetric analyzer (TG), model: Rigaku, produced by Hitachi, Japan;
[0050] The specifications and manufacturer information of various raw materials used in the embodiments of this application are commercially available except for the following special instructions;
[0051] Zinc nitrate hexahydrate (Zn(NO3)2·6H2O) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0052] Polyvinyl alcohol (PVA) was purchased from Sane Chemical Technology Co., Ltd.;
[0053] Cobalt nitrate hexahydrate (Co(NO3)2·6H2O) was purchased from MacLean Biochemical Technology Co., Ltd.;
[0054] 2-Methylimidazole, specification 99%, purchased from Aladdin Reagent Co., Ltd.;
[0055] Anhydrous methanol, all with a specification of 98%, was purchased from San Chemical Technology Co., Ltd.;
[0056] Polysulfone (PSf) ultrafiltration membrane: average pore size 20-30nm, one side is a non-woven fabric layer, provided by Zhongyi Filter Equipment Store, Zhouwangmiao Town, Haining City;
[0057] Trimesic acid (BTC) was purchased from McLean Biochemical Technology Co., Ltd.;
[0058] Polydimethylsiloxane (PDMS) was purchased from Sane Chemical Technology Co., Ltd.
[0059] The embodiment of the present invention provides a method for preparing a continuous MOF membrane with a three-dimensional grid interface, wherein the base membrane of the continuous MOF membrane is formed by laminating a polymer support layer, a polysulfone layer and a non-woven fabric layer arranged in sequence from top to bottom, wherein the polymer support layer is a polydimethylsiloxane layer, and the preparation method comprises the following steps:
[0060] S1. After diffusing the PVA-cobalt ion aqueous solution from the polydimethylsiloxane layer into the base membrane, the first ligand solution is diffused from one side of the non-woven fabric layer into the base membrane to coordinate with the cobalt ions in the PVA-cobalt ion aqueous solution to form an α-Co(OH)2 grid layer on the surface of the polydimethylsiloxane layer.
[0061] Since the cobalt ions in the PVA-cobalt ion aqueous solution will be fixed to the PDMS surface under the action of PVA, the ligand molecules in the first ligand solution will enter the PVA-cobalt ion aqueous solution and react with the fixed metal to form MOFs (such as ZIF-67) on the surface. However, since there is an aqueous solution above the PDMS, MOFs will decompose into two-dimensional nanosheets in the aqueous solution, forming a large-area continuous and dense two-dimensional nanosheet grid layer, avoiding direct contact between the organic solvent and the polymer support in subsequent steps, thereby solving the swelling problem caused by direct contact between the organic solvent and the polymer support.
[0062] In addition, since the first ligand solution diffuses back from the non-woven fabric layer into the base membrane to coordinate with the cobalt ions in the PVA-cobalt ion aqueous solution, some metal ions are not combined with the ligand molecules in the first ligand solution and are embedded in the two-dimensional nanosheet grid layer.
[0063] S2. The base film obtained in step S1 is immersed in a metal salt solution, taken out and dried to anchor the metal ions on the α-Co(OH)2 grid layer.
[0064] In this step, the solvent of the metal salt solution is a mixture of a strong polar solvent and water, and the strong polar solvent is preferably methanol or ethanol. The important thing about the solvent is the ratio of the strong polar solvent to water. If a mixed reagent containing only a strong polar solvent or a high content of a strong polar solvent is used to dissolve the ligand, the strong polar solution will easily cause the interface layer to swell, causing the pre-grown mesh layer to swell, which will make it difficult for the metal ions to be riveted on the mesh layer, making the metal ion load uneven or falling off, resulting in defects in the membrane. If only water is used as a solvent, some ligands will not be dissolved, which will affect the coordination reaction with the metal and is not conducive to the growth of the membrane.
[0065] S3. Soaking the base film obtained in step S2 in a second ligand solution to coordinate with the metal ions riveted on the two-dimensional nanosheet grid layer to obtain the continuous MOF membrane with a three-dimensional grid interface.
[0066] In this step, the metal ions embedded in the grid layer and the metal ions riveted to the two-dimensional nanosheet grid layer are combined with the ligand molecules in the second ligand solution, thereby enhancing the continuity and density of the MOF membrane.
[0067] The above technical implementation scheme will be illustrated by the following examples.
[0068] Preparation of base membrane: One side of the polysulfone (PSf) ultrafiltration membrane is a non-woven fabric layer, and PDMS is coated on the other side of the polysulfone (PSf) ultrafiltration membrane to obtain a base membrane.
[0069] PVA-cobalt ion aqueous solution: 2.5 g of polyvinyl alcohol (PVA) is fully dissolved in 100 mL of deionized water, heated to 95°C and stirred evenly to obtain a PVA aqueous solution; then 3 g of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) is added to the above solution, stirred evenly to form a PVA-cobalt ion aqueous solution.
[0070] Example 1 Preparation of ZIF-67-1
[0071] Preparation of the first ligand solution: 3.2 g of 2-methylimidazole was dissolved in 100 mL of anhydrous methanol to obtain an anhydrous methanol solution of 2-methylimidazole with a mass fraction of 3.2 wt %.
[0072] Preparation of the second ligand solution: 3.2 g of 2-methylimidazole was dissolved in 100 mL of anhydrous methanol to obtain an anhydrous methanol solution of 2-methylimidazole with a mass fraction of 3.2 wt %.
[0073] S01: Fix the base membrane with the PDMS-coated side facing up on a hollow plastic frame, measure 50 mL of PVA-cobalt ion aqueous solution and pour it on the surface of the base membrane (PDMS side), and soak it for 30 minutes, then move it horizontally into the first ligand solution, so that the first ligand solution diffuses from the non-woven fabric side into the base membrane surface (PDMS side), react for 10 seconds, take out the membrane and pour out the excess solution, soak it in clean deionized water, clean it and put it in a constant temperature and humidity chamber at a temperature of 30°C and a humidity of 40°C to dry for 12 hours to obtain a membrane with an α-Co(OH)2-1 grid layer.
[0074] The α-Co(OH)2-1 grid layer was characterized by SEM and AFM. Figure 1 As shown. (1), (2), (3) and (4) are the surface SEM image of the α-Co(OH)2-1 mesh layer at 20μm, the surface SEM image at 400nm, the cross-sectional SEM image at 400nm and the AFM image, respectively. Through the analysis of SEM and AFM images, it can be seen that the surface of the prepared α-Co(OH)2-1 mesh layer has a shallow mesh structure, the film thickness is only 50nm, and the roughness of the film surface is small, only 27.7nm.
[0075] S02: Weigh 3g of Co(NO3)2·6H2O and dissolve it in a solvent with a volume ratio of methanol: water of 1:4, and stir it thoroughly to form a cobalt metal solution. Then fix the α-Co(OH)2-1 grid layer of the membrane obtained in step S1 on a glass plate facing upward, and pour the cobalt metal solution on the membrane to immerse the membrane surface for 4 hours. Then, take out the membrane and put it into an oven at 30°C to dry for 8 hours to form an α-Co(OH)2-1 metal layer.
[0076] S03: Immerse the α-Co(OH)2-1 metal layer of the membrane obtained in step S02 face down in the second ligand solution. After reacting for 4 hours, take out the membrane and place it in a constant temperature and humidity chamber at a temperature of 30°C and a humidity of 40°C to dry for 10 hours to prepare a Z IF-67-1 membrane.
[0077] The ZIF-67-1 membrane obtained above was scanned by SEM and AFM. The obtained SEM images are shown in Figure 2 As shown, Figure 2 -(a) and 2-(b) are SEM images of the membrane surface at 2 μm and 400 nm, respectively. Figure 2 - (c) is a SEM image of the film cross section at 400 nm; Figure 2 - (d) is the AFM image of the film at 2 μm. Figure 2It can be seen from Figures 2-(a) and 2-(b) that when the α-Co(OH)2-1 grid layer is used for the growth of ZIF-67 film, the surface of the ZIF-67-1 film is smooth and has a light granular texture. Figure 2 -(c) shows that the thickness of the ZIF-67-1 film is 58 nm. Figure 2 -(d) shows that the roughness of the obtained ZI F-67-1 film is 48.4 nm, which indicates that the ZI F-67-1 film prepared in Example 1 of the present invention is continuous, dense and thin.
[0078] Example 2Z Preparation of IF-67-2
[0079] Preparation of the first ligand solution: 3.2 g of 2-methylimidazole was dissolved in 100 mL of anhydrous methanol to obtain an anhydrous methanol solution of 2-methylimidazole with a mass fraction of 3.2 wt %.
[0080] Preparation of the second ligand solution: 3.2 g of 2-methylimidazole was dissolved in 100 mL of anhydrous methanol to obtain an anhydrous methanol solution of 2-methylimidazole with a mass fraction of 3.2 wt %.
[0081] S01: Fix the base membrane with the PDMS-coated side facing up on a hollow plastic frame, measure 50 mL of PVA-cobalt ion aqueous solution and pour it on the surface of the base membrane (PDMS side), and after soaking for 30 minutes, move it horizontally into the first ligand solution, so that the first ligand solution diffuses back from the non-woven fabric side into the membrane surface, react for 30 seconds, take out the membrane and pour out the excess solution, soak it in clean deionized water, wash it clean and put it in a constant temperature and humidity box at a temperature of 30°C and a humidity of 40°C to dry for 12 hours to obtain a membrane with an α-Co(OH)2-2 grid layer.
[0082] The above α-Co(OH)2-2 grid layer was tested by SEM, XRD, BET, and TG. The results are as follows: Figure 3 and Figure 4 shown.
[0083] Figure 3 -(a) is a surface image of the α-Co(OH)2-2 grid layer. It can be seen from the image that the membrane surface is flat and has no defects. Figure 3 -(b) is the XRD spectrum of the α-Co(OH)2-2 mesh layer. Compared with the XRD spectrum of the simulated α-Co(OH)2-2 mesh layer, the α-Co(OH)2-2 mesh layer has the same crystal planes at (003) and (006), maintaining a good crystal structure. Figure 3-(c) is the FTIR spectrum of the α-Co(OH)2-2 mesh layer. It can be seen from the figure that the prepared α-Co(OH)2-2 mesh layer has obvious characteristic peaks. Figure 3 -(d) is the TG spectrum of the α-Co(OH)2-2 mesh layer, which shows an obvious decrease in mass percentage at 260°.
[0084] Figure 4 For the morphology characterization of the α-Co(OH)2-2 grid layer, Figure 4 (1), (2), (3) and (4) are the surface SEM images, low-magnification surface SEM images, cross-sectional SEM images and AFM images of the α-Co(OH)2-2 mesh layer, respectively. Through the analysis of SEM and AFM images, it can be seen that with the increase of reaction time, the mesh layer on the membrane surface becomes more obvious, and the thickness of the mesh layer increases significantly, reaching 143nm.
[0085] S02: Weigh 3g Co(NO3)2·6H2O and dissolve it in a solvent with a volume ratio of methanol: water of 1:4, and stir it thoroughly to form a cobalt metal solution. Then fix the dried α-Co(OH)2-2 grid layer on a glass plate facing up, and pour the cobalt metal solution on the membrane. After immersing the membrane surface for 4 hours, take out the membrane and put it into an oven at 30°C to dry for 8 hours to form an α-Co(OH)2-2 metal layer.
[0086] S03: Immerse the α-Co(OH)2-2 metal layer of the membrane obtained in step S02 face down in the second ligand solution. After reacting for 4 hours, take out the membrane and place it in a constant temperature and humidity chamber at a temperature of 30°C and a humidity of 40°C to dry for 10 hours to prepare a Z IF-67-2 membrane.
[0087] The ZIF-67-2 membrane obtained above was scanned using SEM, AFM, BET and gas adsorption isotherm. The obtained SEM images are shown in Figure 5 and Figure 6 As shown, Figure 5 -(a) and 5-(b) are SEM images of the membrane surface at 2 μm and 400 nm, respectively. Figure 5 -c is the SEM image of the film cross section at 100 nm; Figure 5 -d is the AFM image of the film at 2 μm. Figure 5 -(a) and 5-(b), when α-Co(OH)2-2 mesh layer is used to prepare ZI F-67-2 membrane, Figure 5 -(c) shows that the thickness of the ZIF-67-2 film is 163 nm. Figure 5-(d) shows that the roughness of the obtained ZIF-67-2 film is 11.7 nm. This shows that the ZIF-67-2 film prepared in Example 2 of the present invention is continuous and dense, and the film surface presents obvious granularity, and the film thickness is significantly increased, but the roughness of the film surface is significantly reduced. Figure 6 For the structural characterization of ZIF-67-2 membrane; Figure 6 -(a) N2 adsorption-desorption isotherm and specific surface area at 77K; Figure 6 -(b) is the CO2 and N2 gas adsorption isotherms of Z IF-67-2 membrane; Figure 6 -(c) is the CH4 and N2 gas adsorption isotherms of ZIF-67-2 membrane; Figure 6 -(d) is the C3H6 and C3H8 gas adsorption isotherms of ZIF-67-2 membrane. Figure 6 It can be seen that the prepared ZIF-67-2 membrane has a suitable specific surface area of 391.02 m 2 / g, and has obvious separation effect on CO2 / N2, CH4 / N2 and C3H6 / C3H8.
[0088] Example 3Z Preparation of IF-67-3
[0089] Preparation of the first ligand solution: 3.2 g of 2-methylimidazole was dissolved in 100 mL of anhydrous methanol to obtain an anhydrous methanol solution of 2-methylimidazole with a mass fraction of 3.2 wt %.
[0090] Preparation of the second ligand solution: 3.2 g of 2-methylimidazole was dissolved in 100 mL of anhydrous methanol to obtain an anhydrous methanol solution of 2-methylimidazole with a mass fraction of 3.2 wt %.
[0091] S01: Fix the base membrane with the PDMS-coated side facing up on a hollow plastic frame, measure 50 mL of PVA-cobalt ion aqueous solution and pour it on the surface of the base membrane (PDMS side), and soak it for 30 minutes, then move it horizontally into the first ligand solution, so that the first ligand solution diffuses back from the non-woven fabric side into the surface of the base membrane (PDMS side), react for 60 seconds, take out the membrane and pour out the excess solution, soak it in clean deionized water, clean it and put it in a constant temperature and humidity chamber at a temperature of 30°C and a humidity of 40°C to dry for 12 hours to obtain a membrane with an α-Co(OH)2-3 grid layer.
[0092] The α-Co(OH)2-3 mesh layer was characterized by SEM and AFM. Figure 7 As shown. Figure 7In the figure, (1), (2), (3) and (4) are the surface SEM images of the α-Co(OH)2-3 mesh layer at 20μm, the surface SEM images at 400nm, the cross-sectional SEM images at 400nm and the AFM images at 2μm. The SEM and AFM images show that the mesh structure on the surface of the prepared α-Co(OH)2-3 mesh layer is clearly connected, the film thickness is significantly increased to 252nm, and the roughness of the film surface is significantly increased to 107.4nm.
[0093] S02: Weigh 3g of Co(NO3)2·6H2O and dissolve it in a solvent with a volume ratio of methanol: water of 1:4, and stir it thoroughly to form a cobalt metal solution. Then fix the α-Co(OH)2-3 grid layer of the membrane obtained in step S1 on a glass plate facing upward, and pour the cobalt metal solution on the membrane to immerse the membrane surface for 4 hours. Then take out the membrane and put it into an oven at 30°C to dry for 8 hours to form an α-Co(OH)2-3 metal layer.
[0094] S03: Immerse the α-Co(OH)2-3 metal layer of the membrane obtained in step S02 face down in the second ligand solution. After reacting for 4 hours, take out the membrane and place it in a constant temperature and humidity chamber at a temperature of 30°C and a humidity of 40°C to dry for 10 hours to prepare a Z IF-67-3 membrane.
[0095] The ZIF-67-3 membrane obtained above was scanned by SEM and AFM. The obtained SEM images are shown in Figure 8 As shown, Figure 8 -(a) and 8-(b) are SEM images of the membrane surface at 2 μm and 400 nm, respectively. Figure 8 - (c) is a SEM image of the film cross section at 400 nm; Figure 8 - (d) is the AFM image of the film at 2 μm. Figure 8 It can be seen from Figures 8-(a) and 8-(b) that when the α-Co(OH)2-3 mesh layer is used for ZIF-67 film growth, the surface of the ZIF-67-3 film is smooth and has granular accumulation. Figure 8 -(c) shows that the thickness of the ZIF-67-3 film is 282 nm. Figure 8 -(d) shows that the roughness of the obtained ZI F-67-3 film is 15.5 nm, which indicates that the ZI F-67-3 film prepared in Example 3 of the present invention is continuous, dense and thick.
[0096] Example 4Z Preparation of IF-8 membrane
[0097] Preparation of the first ligand solution: 3.2 g of 2-methylimidazole was dissolved in 100 mL of anhydrous methanol to obtain an anhydrous methanol solution of 2-methylimidazole with a mass fraction of 3.2 wt %.
[0098] Preparation of the second ligand solution: 3.2 g of 2-methylimidazole was dissolved in 100 mL of anhydrous methanol to obtain an anhydrous methanol solution of 2-methylimidazole with a mass fraction of 3.2 wt %.
[0099] (1) Weigh 3 g of Zn(NO3)2·6H2O and dissolve it in a solvent with a volume ratio of methanol to water of 1:4, and stir it thoroughly to form a zinc metal solution. Then, fix the α-Co(OH)2-2 grid layer of the membrane obtained in step S1 of Example 2 on a glass plate with the α-Co(OH)2-2 grid layer facing upward, and pour the cobalt metal solution on the membrane to immerse the membrane surface for 4 hours. Then, take out the membrane and put it into an oven at 30°C to dry for 8 hours to form an α-Co(OH)2-Zn metal layer.
[0100] (2) The α-Co(OH)2-Zn metal layer of the membrane obtained in step (1) was immersed in the second ligand solution with the surface facing downward. After reacting for 4 hours, the membrane was taken out and placed in a constant temperature and humidity chamber at a temperature of 30°C and a humidity of 40°C for 10 hours to prepare a ZIF-8 membrane.
[0101] The ZIF-8 film obtained above was scanned by SEM, and the obtained SEM image is as follows: Fig. 9 As shown, Fig. 9 -(a) and 9-(b) are SEM images of the membrane surface at 10 μm and 300 nm, respectively. Fig. 9 -(a) and 9-(b) can be seen that, through the comparison of Example 1.2.3, the optimal α-Co(OH)2-2 grid layer is finally selected for ZIF-8 film growth. The surface of the ZIF-8 film is optically dense, continuous and defect-free, proving that the film preparation method has certain versatility.
[0102] Example 5 Preparation of CuBTC film
[0103] Preparation of the first ligand solution: 3.2 g of 2-methylimidazole was dissolved in 100 mL of anhydrous methanol to obtain an anhydrous methanol solution of 2-methylimidazole with a mass fraction of 3.2 wt %.
[0104] Preparation of the second ligand solution: Weigh 3.2 g of trimesic acid (BTC) and dissolve it in 100 mL of anhydrous methanol reagent, and stir well to form a second ligand solution.
[0105] (1) Weigh 3 g of Cu(NO3)2·3H2O and dissolve it in a solvent with a volume ratio of methanol to water of 1:4, and stir it thoroughly to form a copper metal solution. Then, fix the α-Co(OH)2-2 grid layer of the membrane obtained in step S1 of Example 2 on a glass plate with one side facing up, and pour the copper metal solution on the membrane to immerse the membrane surface for 4 hours. Then, take out the membrane and put it into an oven at 30°C to dry for 8 hours to form an α-Co(OH)2-Cu metal layer.
[0106] (2) The α-Co(OH)2-Cu metal layer of the membrane obtained in step (1) was immersed in the second ligand solution with one side facing downward. After reacting for 4 hours, the membrane was taken out and placed in a constant temperature and humidity chamber at a temperature of 30°C and a humidity of 40°C for 10 hours to prepare a CuBTC membrane.
[0107] The CuBTC film obtained above was scanned by SEM, and the obtained SEM image is as follows: Fig.10 As shown, Fig.10 -(a) and 10-(b) are SEM images of the membrane surface at 4 μm and 400 nm, respectively. Fig.10 -(a) and 10-(b), it can be seen that when the α-Co(OH)2-2 grid layer is selected for CuBTC film growth, the CuBTC film also has the characteristics of being dense, continuous and having excellent crystals.
[0108] Comparative Example 1Z Preparation of IF-67-4
[0109] (1) Weigh 3 g of Co(NO3)2·6H2O and dissolve it in a solvent with a volume ratio of methanol to water of 1:1, and stir it thoroughly to form a cobalt metal solution. Then, the α-Co(OH)2-2 grid layer of the membrane obtained in step S1 of Example 2 is fixed on a glass plate with the α-Co(OH)2-2 grid layer facing upward, and the cobalt metal solution is poured on the membrane to immerse the membrane surface for 4 hours. The membrane is then taken out and placed in an oven at 30°C for 8 hours to form an α-Co(OH)2-4 metal layer.
[0110] (2) The α-Co(OH)2-4 metal layer of the membrane obtained in step (1) was immersed in the second ligand solution with one side facing downward. After reacting for 4 hours, the membrane was taken out and placed in a constant temperature and humidity chamber at a temperature of 30°C and a humidity of 40°C for 10 hours to prepare a ZIF-67-4 membrane.
[0111] The ZIF-67-4 membrane obtained above was scanned by SEM, and the obtained SEM image is as follows: Fig.11 As shown, Fig.11 -(a) and 11-(b) are SEM images of the membrane surface at 10 μm and 400 nm, respectively. Fig.11-(a) and 11-(b), it can be seen that when the α-Co(OH)2-2 grid layer is used to grow the ZIF-67-4 membrane, the ZIF-67-4 membrane shows obvious swelling on the membrane surface due to the use of a solvent with a volume ratio of 1:1 of methanol: water in the preparation of the α-Co(OH)2-4 metal layer, which leads to reduced anchoring of copper metal ions, thereby affecting the nucleation growth of MOFs on the membrane surface, resulting in obvious defects in the prepared membrane.
[0112] Comparative Example 2Z Preparation of IF-67-5
[0113] (1) Weigh 3 g of Co(NO3)2·6H2O and dissolve it in a solvent with a volume ratio of methanol to water of 1:2, and stir it thoroughly to form a cobalt metal solution. Then, fix the dried α-Co(OH)2-2 mesh layer on a glass plate, and immerse the cobalt metal solution on the membrane surface for 4 h. Then, take out the membrane and put it into an oven at 30°C to dry for 8 h to form an α-Co(OH)2-5 metal layer.
[0114] (2) The α-Co(OH)2-5 side of the membrane obtained in step (1) was immersed in the second ligand solution with the surface facing downward. After reacting for 4 hours, the membrane was taken out and placed in a constant temperature and humidity chamber at a temperature of 30°C and a humidity of 40°C to dry for 10 hours to prepare a ZIF-67-5 membrane.
[0115] The ZIF-67-5 membrane obtained above was scanned by SEM, and the obtained SEM image is as follows: Fig.12 As shown, Fig.12 -(a) and 12-(b) are SEM images of the membrane surface at 2 μm and 600 nm, respectively. Fig.12 -(a) and 12-(b) can be seen that when the α-Co(OH)2-2 grid layer is selected for the growth of the ZIF-67-5 film, the ZIF-67-5 film also shows obvious cracks and looseness because a solvent with a volume ratio of methanol: water of 1:2 is used in the preparation of the α-Co(OH)2-5 metal layer, which results in a low content of metal ions on the membrane surface. Therefore, Comparative Examples 1 and 2 fully illustrate that when preparing the α-Co(OH)2 metal layer, excessively high methanol content will seriously affect the rivets of metal ions, thereby affecting the density and continuity of the membrane.
[0116] Test Case
[0117] For single gas permeation measurements, the membranes were mounted in stainless steel cells (effective membrane area = 0.25 cm 2 ), and the raw gas pressure is maintained at 0.5-2.0 bar (gauge pressure, transmembrane pressure), which is controlled by a precise pressure gauge.
[0118] The flux of permeated gas was measured by a soap bubble flowmeter, and the gas permeability R (GPU, 1GPU = 1×10 -6 cm 3 (STP) cm -2 ·s -1 cmHg -1 =3.35×10 -10 mol·s -1 ·m -2 ·Pa -1 ) by the formula definition.
[0119] Where N i (mols -1 ) is the molar flow rate of permeating component i, A(m 2 ) is the effective membrane area, Δp i (Pa) is the pressure difference between membranes. Ideal selectivity α i / j The permeability ratio of gas component i to component j is calculated according to the formula calculate.
[0120] The mixed gas permeability was measured using a laboratory-made stainless steel instrument at 30°C and 0.5-2.0 bar with a mixture of dry C3H6 / C3H8 (50 / 50 volume), CH4 / N2 (50 / 50 volume) and CO2 / N2 (50 / 50 volume). The membrane gas permeability was measured using a constant pressure test device. The total feed gas flow rate was 40 mL min -1 The transmembrane pressure is controlled by the back pressure valve on the feed side. Dry helium is used as the downstream sweep gas (50 mL min -1 ) carries the permeate gas into the gas chromatograph. The downstream sweep gas components are analyzed using a gas chromatograph equipped with a thermal conductivity detector (HP7890, Porapak N). Three different samples are measured for each membrane, and 18 points are selected for each sample to obtain the average permeate data and its standard deviation.
[0121] The permeation rates and gas separation selectivities of the ZIF-67-1 membrane, ZIF-67-2 membrane, and ZIF-67-3 membrane obtained in Examples 1-3 were measured under pure gas conditions. The measured data results are shown in FIG. Fig.13 As shown. Among them, Fig.13 -(a) is the permeation rate of CH4 for ZIF-67-1, ZIF-67-2, and ZIF-67-3 membranes under pure gas conditions; Fig.13 -(b) N2 permeation rate of ZIF-67-1, ZIF-67-2, and ZIF-67-3 membranes under pure gas conditions; Fig.13-(c) CH4 / N2 separation selectivity of ZIF-67-1, ZIF-67-2, and ZIF-67-3 membranes under pure gas conditions.
[0122] from Fig.13 It can be seen that the ZIF-67-1 membrane, ZIF-67-2 membrane, and ZIF-67-3 membrane of the present application separate CH4 and N2 at different pressures. Under 2 bar conditions, the CH4 permeation rates are 3515.5 GPU, 2789.27 GPU, and 2581.75 GPU, respectively, and the CH4 / N2 selectivities are 5.76, 8.00, and 8.42, respectively. It can be seen from the performance characterization that with the increase of the 2-methylimidazole immersion time during the preparation of the α-Co(OH)2-2 mesh layer, the permeation rate of the prepared membrane decreases significantly, but the gas separation selectivity of the membrane increases significantly, which indicates that the gas separation performance of the MOF membrane obtained by the preparation method of the MOF membrane of the present application does not increase with the increase of the 2-methylimidazole immersion time.
[0123] Based on the good gas separation selectivity of the prepared membrane for CH4 / N2, the CO2 / N2 separation selectivity was further tested. Fig.14 As shown. Among them, Fig.14 -(a) is the permeation rate of CO2 of ZIF-67-1, ZIF-67-2, and ZIF-67-3 membranes under pure gas conditions; Fig.14 -(b) N2 permeation rate of ZIF-67-1, ZIF-67-2, and ZIF-67-3 membranes under pure gas conditions; Fig.14 -(c) ZIF-67-1, ZIF-67-2, and ZIF-67-3 membranes for CO2 / N2 separation selectivity under pure gas conditions. Fig.14 It can be seen that the ZIF-67-1 membrane, ZIF-67-2 membrane, and ZIF-67-3 membrane in this application separate CO2 and N2 at different pressures. Under 2 bar conditions, the CO2 permeation rates are 8661GPU, 8238GPU, and 7933.5GPU, respectively, and the CO2 / N2 selectivities are 14.18, 23.68, and 25.88, respectively. Similarly, with the increase in the immersion time of the first ligand solution during the preparation of the α-Co(OH)2-2 mesh layer, the permeation rate of the prepared membrane decreases significantly, but the gas separation selectivity of the membrane increases significantly. By comparing the membrane performance, while ensuring high gas separation selectivity, a high permeation rate is also required. Therefore, the preparation conditions of the ZIF-67-2 membrane are finally selected as the optimal conditions.
[0124] Through the above comparison, we tested the C3H6 / C3H8 separation selectivity of ZIF-67-2 membrane. The results are as follows: Fig.15 . Fig.15 -(a) The permeation rate of ZIF-67-2 membrane to C3H6 and C3H8 and the separation selectivity of C3H6 / C3H8 under pure gas conditions; Fig.15 -(b) The permeation rate of ZIF-67-2 membrane to C3H6 and C3H8 under mixed gas conditions and the separation selectivity of C3H6 / C3H8. Under pure gas conditions of 2 bar, the C3H6 permeation rate of ZIF-67-2 membrane is 6778.195 GPU, and the C3H6 / C3H8 separation selectivity is 19.555; under mixed gas conditions of 2 bar, the C3H6 permeation rate of ZIF-67-2 membrane is 6602.57 GPU, and the C3H6 / C3H8 separation selectivity is 18.855. The test results of different gas systems show that the membrane preparation method in this application has excellent gas separation performance.
[0125] Based on this method, we conducted tests on CuBTC membranes, such as Fig.16 As shown, the CuBTC membrane has excellent gas separation selectivity for CH4 / N2, CO2 / N2, and C3H6 / C3H8. Fig.16 -(a) The permeation rate of CH4 and N2 and the separation selectivity of CH4 / N2 of CuBTC membrane under pure gas conditions; Fig.16 -(b) The permeation rate of CO2 and N2 and the separation selectivity of CO2 / N2 of CuBTC membrane under pure gas conditions; Fig.16 -(c) CuBTC membrane permeation rate of C3H6 and C3H8 and separation selectivity of C3H6 / C3H8 under pure gas conditions. Among them, under the pure gas test condition of 2 bar, the CH4 permeation rate of the membrane is 763.67 GPU, and the CH4 / N2 selectivity is 1.91; the CO2 permeation rate of the membrane is 7745.125 GPU, and the CO2 / N2 selectivity is 19.73; the C3H6 permeation rate of the membrane is 7003.665 GPU, and the C3H6 / C3H8 selectivity is 13.16. The test characterization proves that other types of MOF membranes prepared by this method also have good gas separation selectivity.
[0126] In summary, the present invention discloses a method for preparing a continuous MOF membrane having a three-dimensional grid interface, which is carried out at room temperature throughout the process. First, the unstable characteristics of ZIF-67 are utilized to form a large area of defect-free α-Co(OH)2 nanosheet grid layer on the surface of the polymer support. Since the α-Co(OH)2 grid layer exhibits hydrophobic properties, the appropriate ratio of water and methanol in the preparation can effectively solve the swelling problem of the polymer support, further play the role of pre-embedded metal in the grid layer, strengthen heterogeneous nucleation on the interface layer, and realize the preparation of different types of MOF membranes on the polymer support. In addition, based on the two-dimensional α-Co(OH)2 grid layer, a three-dimensional MOF membrane is prepared on the two-dimensional structure by the gradient body mutual phase diffusion method, realizing a continuous and dense MOF membrane combining two-dimensional and three-dimensional, and the prepared membrane has excellent separation selectivity for different gas systems.
[0127] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A method for preparing a continuous MOF membrane with a three-dimensional grid interface, wherein the base membrane of the continuous MOF membrane is formed by laminating a polymer support layer, a polysulfone layer and a non-woven fabric layer arranged in sequence from top to bottom, characterized in that: The polymer support layer is a polydimethylsiloxane layer, and the preparation method comprises the following steps: S1. After diffusing the PVA-cobalt ion aqueous solution from the polydimethylsiloxane layer into the base film, diffusing the first ligand solution from the non-woven fabric layer into the base film to coordinate with the cobalt ions in the PVA-cobalt ion aqueous solution, forming an α-Co(OH)2 grid layer on the surface of the polydimethylsiloxane layer, and obtaining a membrane having an α-Co(OH)2 grid layer; S2. The membrane having the α-Co(OH)2 mesh layer is immersed in a metal salt solution to fix the metal ions in the metal salt solution on the α-Co(OH)2 mesh layer. The membrane is taken out and dried, and then immersed in a second ligand solution for reaction to obtain the continuous MOF membrane having a three-dimensional mesh interface.
2. The preparation method according to claim 1, characterized in that: Step S1 specifically comprises: fixing the polydimethylsiloxane layer of the base film in the air with the polydimethylsiloxane layer facing upward, pouring the PVA-cobalt ion aqueous solution from the polydimethylsiloxane layer and soaking for 30-50 minutes, then moving it horizontally into the first ligand solution, soaking for 10-60 seconds, taking it out, washing it, and drying it.
3. The preparation method according to claim 1, characterized in that: In step S2, the soaking in the second ligand solution specifically includes soaking the polydimethylsiloxane layer downward in the second ligand solution for reaction for 3-6 hours.
4. The preparation method according to claim 1, characterized in that: The solvent of the first ligand solution is methanol or ethanol.
5. The preparation method according to claim 1, characterized in that: The ligand in the first ligand solution is 2-methylimidazole.
6. The preparation method according to claim 1, characterized in that: The metal salt solution is a cobalt salt solution or a zinc salt solution, and the ligand in the second ligand solution is 2-methylimidazole; or, The metal salt solution is a copper salt solution, and the ligand in the second ligand solution is trimesic acid.
7. The preparation method according to claim 6, characterized in that: The solvent of the metal salt solution is a mixture of a strong polar solvent and water, and the strong polar solvent is methanol or ethanol.
8. The preparation method according to claim 7, characterized in that: The volume ratio of the strong polar solvent to water is 1:(1-4).
9. A continuous MOF film having a three-dimensional grid interface prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the continuous MOF membrane with a three-dimensional grid interface according to claim 9 in gas separation.
Citation Information
Patent Citations
Preparation method of polymer-based metal organic framework hybrid membrane
CN106823854A
Preparation method of metal organic framework membrane
CN112246111A
Metal-organic framework supported on porous polymer
US20130313193A1
Porous membrane containing metal-organic frameworks
US20200269194A1